Exponential stability analysis of Timoshenko beam system with boundary delays. Issue 15 (18th November 2017) - Tian, Zongfei; Xu, Gen-Qi
Abstract : In this paper, we investigate the exponential stability of Timoshenko beam system with interior damping and boundary delays. At first, applying the semigroup theory of bounded linear operators we prove the well-posedness of the system. And then we give the exponential stability analysis of the system by constructing an appropriate Lyapunov function. Different from the earlier results, we use the damping coefficients and delay coefficients together with the parameters of the system to give a description of the stability region.